Study on the Relationship of Ions (Na, K, Ca) Absorption and Distribution to Photosynthetic Response of Salix matsudana Koidz Under Salt Stress - Ran, Xin; Wang, Xiao; Huang, Xiaoxi; Ma, Changming; Liang, Haiyong; Liu, Bingxiang (Frontiers in Plant Science, 2022)
In order to screen out the key indicators for salt tolerance evaluation of Salix matsudana Koidz, we explored the relationship of ion absorption and distribution to chlorophylls, fluorescence parameters (leaf performance index, maximum photochemical efficiency), and photosynthetic gas parameters (net photosynthetic rate, transpiration, stomatal conductance, intercellular carbon dioxide concentration) under salt stress. We set up 4 groups and one control group as per salinity levels of NaCl hydroponic solutions (171mm, 342mm, 513mm and 684mm). The Na+/K+, Na+/Ca2+, chlorophyll fluorescence and photosynthetic parameters of leaves were measured on the 1st, 3rd, 5th, 8th, 11th and 15th days respectively for an analysis of the correlations of chlorophylls, chlorophyll fluorescence and photosynthetic parameters to ion distribution ratio. The results showed: 1) The ratio of dry weight of roots to leaves gradually increased with the increase of salt concentration, while the water content of leaves and roots firstly increased and then decreased with the increase of time.; 2) The content of Na+、Na+/K+ and Na+/Ca2+ in roots and leaves rose with the increase of salt stress concentration and treatment time, and the difference gradually narrowed. 3) Ca2+ was lost more than K+ under salt stress, and Na+/Ca2+ was more sensitive to the salt stress environment than Na+/K+; 4) Because the root system had a retention effect, both Na+/K+ and Na+/Ca2+ in roots under different NaCl concentrations and different treatment time were higher than those in leaves, and Na+/Ca2+ was much higher than Na+/K+ in roots; 5) Na+/K+ had a higher correlation with fluorescence parameters than Na+/Ca2+. Among them, Na+/K+ had a significantly negative correlation with the maximum photochemical efficiency, and the correlation coefficient R2 was 0.8576; 6) Photosynthetic gas parameters had a higher correlation with Na+/Ca2+ than with Na+/K+. Among them, there were significantly negative correlations between Na+/Ca2+ and Gs, as well as between Na+/Ca2+ and E under salt stress. The correlation between Na+/Ca2+ and Gs was the highest, with a correlation coefficient of 0.9368; 7) Na+/K+ and Na+/Ca2+ had no significant difference in correlation with chlorophylls. Na+/Ca2+ was selected as a key index to evaluate the salt tolerance of Salix matsulosa Koidz.